Allan Stoekl. The Three Sustainabilities: Energy, Economy, Time. U of Minnesota P, 2021. - Martin A Hipsky (Studies in 20th & 21st Century Literature, 2024)
Review of Allan Stoekl. The Three Sustainabilities: Energy, Economy, Time. U of Minnesota, 2021. 297 pp.